Addressing Occupational Performance Deficits in a Religious Setting: A Pediatric Case Report - Bryan M. Gee; Daniel Leatham (Scholarworks @ WMU, 2022)
Background: The purpose of this pediatric case report is to document how occupational therapy assisted a family with a child who has a diagnosis of ASD and the religious clergy increase the child's participation in activities in the religious context. Method: The pediatric case report uses an exploratory approach to explore the process of evaluating challenging psychosocial behaviors and implementing contextual and personal strategies to increase participation in meaningful occupations. Results: As a result of the occupational therapy recommendations and follow-up consultations, the client demonstrated a reduction in behaviors that were a barrier to her participation in meaningful activities in a religious context. Most notably observed were reductions with verbalizations, excessive movement, verbal outbursts (high volume), wandering, and fighting. Conclusions: Occupational therapists have a role in addressing the behavioral and emotional challenges that may prevent children with ASD from participating in meaningful religious activities valued by families and their communities. The strategies recommended as a part of this case report represent strategies commonly used in the home, community, and school-based settings. However, this case pediatric report highlights the application of psychosocial/behavioral and contextual recommendations in religious contexts.